DEVELOPMENT AND IN VITRO EVALUATION OF RED RASPBERRY FRUIT EXTRACT O/W COSMETIC EMULGEL (International Journal of Pharmacy & Integrated Health Sciences, 2021)
Background and objective: The object of this study was to develop a stable O/W (oil-in-water) cosmetic emulgel of red raspberry fruit extract and its in vitro evaluation. Methodology: A base with no plant extract and a formulation with 4% extract of red raspberry were prepared and kept at different storage conditions in stability chambers i.e., 8, 25, and 40 °C, and 40 °C ±75% RH for a period of 12 weeks. Stability parameters i.e. color, phase separation, liquefaction, pH and electrical conductivity tests were performed at interval of 0, 24, 48, 72h and 7, 14, 21, 28, 45, 60, 75 and 90 days. Results: The results showed that there were unchanged organoleptic properties in terms of appearance, color and odor, unchanged properties after centrifugation and phase separation, and in terms of electrical conductivity and liquefaction. Significant change in pH of base and active formulation were observed with the passage of time. Conclusion: As a conclusion of this work a stable topical formulation of O/W emulgel carrying red raspberry fruit extract can be formulated and can be used for cosmetic purposes.